Coulomb Effect in the Hybrid Double Quantum Dot–Metal Nanoparticle Systems - Nour A. Nasser; Amin H. Al-Khursan (Advances in Condensed Matter Physics)
The scattering rates under Coulomb interaction in the double quantum dot (DQD)–metal nanoparticle (MNP) structure, which were not specified earlier, are modeled. These rates are significant in knowing how the processes in such systems occur and which specific structure is adequate for the required application. The capture and relaxation rates are derived first, and the MNP potential is formulated for the first time. These rates are then introduced into the density matrix formalism of the system. One must refer to the reduced in-capture rates for electrons compared to holes. The relaxation rates are lower than the capture rates, indicating that the structure is not a loser. The DQD behavior is specified. The importance of the MNP potential in increasing the capture rates is detected. The scattering rates are reduced with increasing MNP radius. The electron capture times appear in a range of 10–30 ns, referring to more confinement of the carriers in the QDs under the MNP effect. The results are compared to those of the literature.